Selection and Recommendation Scholarships Using AHP-SVM-TOPSIS - Putra, M Gilvy Langgawan; Ariyanti, Whenty; Cholissodin, Imam (Journal of Information Technology and Computer Science, 2016)
Abstract. Gerakan Nasional Orang Tua Asuh Scholarship offers a number of scholarship packages. As there are a number of applicants, a system for selection and recommendation is required. we used 3 methods to solve the problem, the methods are AHP for feature selection, SVM for classification from 3 classes to 2 classes, and then TOPSIS give a rank recommendation who is entitled to receive a scholarship from 2 classes. In testing threshold for AHP method the best accuracy 0.01, AHP selected 33 from 50 subcriteria. SVM has highest accuracy in this research is 89.94% with Sequential Training parameter are Î» =0.5, constant of Î³ =0.01 , Îµ = 0.0001, and C = 1. Keywords: Selection, Recommendation, Scholarships, AHP-SVM-TOPSIS